Relation between metabolic syndrome and body compositions among Chinese adolescents and adults from a large-scale population survey - Tao Xu; Junting Liu; Junxiu Liu; Guangjin Zhu; Shaomei Han (BMC, 2017)
Abstract Background Few nationally representative surveys regarding body composition and metabolic syndrome (MetS) have been done in a large-scale representative Chinese population to explore the prediction of body composition indicators for MetS. The objective of this study was to examine the relation of body composition and MetS and to determine the optimal cut-off values of body composition indicators that predict MetS in a large representative Chinese sample based on multiple provinces and ethnicities, covering a broad age range from 10 to 80 years old. Methods The subjects came from a large-scale population survey on Chinese physiological constants and health conditions conducted in six provinces. 32,036 subjects completed all blood biochemical testing and body composition measure. Subjects meeting at least 3 of the following 5 criteria qualify as having MetS: elevated blood pressure, lower high density lipoprotein cholesterol level, higher triglyceride level, higher fasting glucose level and abdominal obesity. Results The total prevalence rate of MetS for males (9.29%) was lower than for females (11.58%). The prevalence rates were 12.03% for male adults and 15.57% for female adults respectively. The risk of MetS increased 44.6% (OR = 1.446, 95%CI: 1.414-1.521) for males and 53.4% (OR = 1.534, 95%CI: 1.472-1.598) for females with each 5% increase of percentage of body fat. The risk of MetS increased two-fold (OR = 2.020, 95%CI: 1.920-2.125 for males; OR = 2.047, 95%CI: 1.954-2.144 for females respectively) with each 5% increase of waist-hip ratio. The risk of MetS increased three-fold (OR = 2.915, 95%CI: 2.742-3.099 for males; OR = 2.950, 95%CI: 2.784-3.127 for females respectively) with each 5% increase of Waist-to-Height Ratio (WHtR). Areas under the receiver operating curve (AUC) of most body composition indicators were larger than 0.70 and the sensitivities and the specificities of most cut-off values were larger than 0.65. AUCs of WHR and WHtR were the largest. The optimal cut-off values of WHtR were 0.51 for males and 0.53 for females. Conclusion MetS has become a serious public health challenge in China. Body composition variables were closely related to MetS and they were reliable indicators in the screening of the presence of MetS.